2005
DOI: 10.1529/biophysj.104.044974
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Axial Current in Chara corallina Reflects the Altered Kinetics of Ions in Cytoplasm under the Influence of Light

Abstract: Recent experiments demonstrate that the concentration of Ca2+ in cytoplasm of Chara corallina internodal cells plays important role in electrical excitation of the plasma membrane. The concentration of free Ca2+ in the cytoplasm -[Ca2+]c is also sensitive to visible light. Both phenomena were simultaneously studied by noninvasive measuring action potential (AP) and magnetic field with a superconducting quantum interference device magnetometer in very close vicinity of electrically excited internodal C. coralli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For example, in Chara corallina , the action potential is not based only on voltage-dependent ion channels; the exposure to light causes a progressive shift in the depolarization maximum. 132 But this complexity does not signify a difference between plants and animals because some neurons in animals also have action potentials that are not entirely based on time- and voltage-dependent ion channels. 133 A recent study in Nitellopsis obtusa and Marchantia polymorpha has shown that inhibitors of human two-pore channels alter resting potential, action potential amplitudes and the duration of action potential repolarization by affecting channels.…”
Section: The Definition Of a Nervous Systemmentioning
confidence: 99%
“…For example, in Chara corallina , the action potential is not based only on voltage-dependent ion channels; the exposure to light causes a progressive shift in the depolarization maximum. 132 But this complexity does not signify a difference between plants and animals because some neurons in animals also have action potentials that are not entirely based on time- and voltage-dependent ion channels. 133 A recent study in Nitellopsis obtusa and Marchantia polymorpha has shown that inhibitors of human two-pore channels alter resting potential, action potential amplitudes and the duration of action potential repolarization by affecting channels.…”
Section: The Definition Of a Nervous Systemmentioning
confidence: 99%
“…1,2 In addition to the SQUID's unsurpassed field sensitivity, this technique is completely non-invasive and can be implemented to study a great variety of samples. RT sample SSM is continuing to play an important role in biomagnetism, [3][4][5][6][7][8] nondestructive evaluation, [9][10][11][12][13][14] and geomagnetism. 15,16 Since the field and spatial resolution are highly diminished as the distance between the sample and the sensor increases, the key to this technique is to bring the sensor, held at cryogenic temperatures, as close as possible to the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Although human and animal biomagnetism are well-developed areas of research 2,20,21,24,25,26 , very little analogous work has been conducted in the plant kingdom 9,12,22,27 , largely because biomagnetic signals are typically much smaller in amplitude and frequency than their animal counterparts. Previously reported detection of plant biomagnetism, which established the existence of measurable magnetic activity in the plant kingdom, was carried out using superconducting-quantum-interference-device (SQUID) magnetometers 9,12,22 . Atomic magnetometers are arguably more attractive for biological applications, since, unlike SQUIDs 28,29 , they are non-cryogenic and can be miniaturized to optimize spatial resolution of measured biological features 20,26,30 .…”
Section: Discussionmentioning
confidence: 99%